2005
DOI: 10.1177/0954008305055556
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Biphenyl Polyimides. (I) Chemical Structure-property Relationships

Abstract: A series of polyimides (PIs) were prepared from three biphenyltetracarboxylic dianhydrides (BPDA) isomers, i.e., 3,3′,4,4′-BPDA (s-BPDA), 2,3,3′,4′-BPDA (a-BPDA), and 2,2′',3,3′'-BPDA (iBPDA) with various diamines through the conventional two step process. Polymerization reactivity, solubility, and dynamic mechanical properties (T g, softening behavior, and storage modulus at glassy state) were compared between PIs derived from these BPDA isomers and para/meta diamine isomers. The solubility in NMP increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The a-BPDA/ meta-diamine-based PIs showed a higher storage modulus measured by DMA as well as a higher tensile modulus. This phenomenon may be explained by a mechanism that a segment containing the meta-linkages can take a more extended conformation form than that containing the para-linkages [7][8]. However, this tendency is hard to distinguish in copolyimides based on mixed-TDPA, which may be attributed to that additional monomers disrupt the conformational consistency resulting in the loss of tensile modulus.…”
Section: Tensile Properties Of Homo-and Co-polyimides Based On Mixed-mentioning
confidence: 89%
See 1 more Smart Citation
“…The a-BPDA/ meta-diamine-based PIs showed a higher storage modulus measured by DMA as well as a higher tensile modulus. This phenomenon may be explained by a mechanism that a segment containing the meta-linkages can take a more extended conformation form than that containing the para-linkages [7][8]. However, this tendency is hard to distinguish in copolyimides based on mixed-TDPA, which may be attributed to that additional monomers disrupt the conformational consistency resulting in the loss of tensile modulus.…”
Section: Tensile Properties Of Homo-and Co-polyimides Based On Mixed-mentioning
confidence: 89%
“…It was reasoned that introduction of the monomers containing asymmetric or noncoplanar structure to replace the linear symmetrical dianhydride in polymer chain could weaken the interchain interaction thus enhancing the solubility and melt flowability [6]. As of result of that, it has been further demonstrated that replacement of the symmetrical dianhydride in PIs with asymmetric ones decreases the melt viscosity but increases the T g relative to the corresponding symmetrical PIs [4,[7][8][9]. Thioetherdiphthalic anhydride (TDPA) is an aromatic bridged dianhydride which has three isomers as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a large drop was clearly apparent in the E' curve of PI(a-ODPA/4,4'-ODA) above Tg with a short rubbery plateau. As in the BPDA based PI systems [4], these observed behaviors are attributed to the rotational inflexibility and irregular geometry of asymmetric ODPA, which means that this asymmetric polyimide can be heat-sealable in the temperature region > 340℃.…”
Section: Preparation Of Isas-tpi Film (Imidization Methods 2mentioning
confidence: 99%
“…In addition, the asymmetric PIs indicate higher thermoplasticity than that of the corresponding symmetric PIs based on their nonplanar biphenylimide structures inhibiting intermolecular interaction (no ordered structure formation). Consequently, the sterically bent/distorted but rotation-restricted structural unit induced by asymmetric aromatic monomers was strongly anticipated for development of new high-performance polyimides [3,4]. We have also invented asymmetric aromatic addition-type imide oligomers (TriA-PI: a-BPDA/4.4'-ODA/PEPA) having high Tg and good processability [5].…”
Section: Introductionmentioning
confidence: 99%
“…The mold patterns could not be imprinted sufficiently due to the low mobility. Upilex-R polyimide shows high modulus of 10 7 Pa even at 370 ℃, which is much higher than the Tg [11]. Figure 1.…”
Section: Direct Imprint To Upilex-r Polyimidementioning
confidence: 99%